Uji Efektivitas Analgetik Ekstrak Etanol Buah Kundur (Benincasa hispida (Thunb.) Cogn.) Terhadap Tikus Putih Jantan (Rattus norvegicus L.) yang Diinduksi Asam Asetat - Gunawan, Muhammad; Fatimah, Cut; Santika, Dewi (Journal of Pharmaceutical and Health Research, 2024)
The class of drugs known as analgesics work by reducing or inhibiting pain. This can be achieved in several ways, such as by preventing the synthesis of prostaglandins, which are mediators of pain perception, or by reducing the sensitivity of pain receptors to mechanical, thermal, electrical stimuli. Interest in using natural-based medicine for therapy is increasing in Indonesian society. Kundur fruit is one of the medicinal plants that can be used as an analgesic. It has been empirically proven that kundur fruit (Benincasa hispida (Thunb.) Cogn.) can reduce pain. The purpose of this study was to ensure that the preparation of simplisia, macroscopic and microscopic analysis, phytochemical screening of simplisia, and analgesic efficacy tests were carried out experimentally in this study. Acetic acid 0.5% was injected intraperitoneally under the abdomen of male white rats to stimulate the male white rats. oral administration of ethanol extract solution of kundur fruit at doses of 100 mg/kgBB, 200 mg/kgBB, 400 mg/kgBB, CMC 0.5% (blank) and metampirone 45 mg/kgBB For one hour the number of writhing animals was counted every ten minutes. In addition, the collected data were statistically examined using Tukey test and SPSS ver. 20 One Way ANOVA. Analysis of simplisia and ethanol extracts of kundur fruit had phytochemical screening for the presence of alkaloids, flavonoids, tannins, saponins, steroids and glycosides. The percentage of writhing reduction increased with increasing doses of bamboo randu herb decoction, indicating an increase in analgesic potential and efficacy. Based on the results of the Tukey test and One Way ANOVA test, a dose of 400 mg/kgBB has the best analgesic potential at the 50th minute and is not statistically different from metampirone 45 mg/kgBB.